Remembering the story of Israel: historical summaries and memory formation in Second Temple Judaism - Buster, Aubrey E. (Cambridge University Press, 2022)
In this book, Aubrey Buster demonstrates how methods adapted from cultural and social memory studies and the new formalism can illuminate the communal function of biblical and extra-biblical historical summaries in Second Temple Judaism. Refining models drawn from memory studies, she applies them to ancient texts and demonstrates the development of Judah's speech about their past across the Second Temple period. Buster's wide-ranging study demonstrates how and where the historical summary functions in the book of Psalms, Nehemiah, 1 and 2 Chronicles, as well as the Qumran Psalms Scrolls, Words of the Luminaries, Paraphrase of Genesis and Exodus, and Pseudo-Daniel. She shows how the historical summary proves to be a generative, replicable, and ultimately productive form of memory. Crossing the boundaries of genre categories and time periods, liturgical performances, and literary works, historical summaries crafted a highly selective but broadly useful mode of commemoration of key events from Israel's past.